307 Is Catheter Diagnostic Cerebral Angiography Still Essential for Patients With Spontaneous Perimesencephalic Subarachnoid Hemorrhage and Negative Computed Tomography Angiogram?. (August 2016) - Galal, Ahmed; ElSerry, Tarek H.; Aziz, Mohamed Mostafa
Abstract : INTRODUCTION: Computed tomography (CT) angiography is currently used as the initial diagnostic tool in patients with spontaneous subarachnoid hemorrhage. Eighty-five percent of spontaneous subarachnoid hemorrhages are reported in the literature as caused by a ruptured aneurysm, whereas 10% are termed nonaneurysmal perimesencephalic subarachnoid hemorrhage and carry and excellent prognosis. This retrospective study was conducted to better clarify the diagnostic yield of transfemoral catheter cerebral angiography in light of the current high-quality CT angiogram imaging reported as negative in cases presenting with perimesencephalic subarachnoid hemorrhage. METHODS: Patients with an admission diagnosis of perimesencephalic subarachnoid hemorrhage and a CT angiogram report as being negative from January 2013 to December 2015 were retrospectively reviewed. CT angiogram findings were correlated with that of the catheter-based diagnostic cerebral angiogram that was done at the time of presentation. Clinical data recorded included age, sex, medical history, and clinical presentation. The authors retrospectively reviewed CT brain, CT angiogram, and digital subtraction angiography images as well as formal reports. RESULTS: A total of 43 patients fulfilled the aforementioned diagnostic criteria of spontaneous perimesencephalic subarachnoid hemorrhage. There were 31 females and 12 males. Ages ranged from 23 to 69 years. All patients had Hunt and Hess grades I or II. There was a false-negative CT angiogram in 4 cases (9.3%) where an underlying aneurysm was identified on digital subtraction angiography, the site of which correlated with the pattern of bleeding. The mean aneurysm size was 2 mm. No complications were related to the catheter angiogram procedure. CONCLUSION: This study shows that CT angiography, even when read as "negative" for cases assumed to have a benign perimesencephalic pattern of subarachnoid hemorrhage, is still insufficient to exclude underlying pathology as the source of hemorrhage. This study showed a "false-negative" CT angiogram read of 9.3%. Although false negatives are very low, indicating a high negative predictive value of CT angiograms, its dependability in excluding underlying pathology is still not 100% when the question involves a life-threatening pathology as a ruptured cerebral aneurysm. Digital subtraction angiogram still remains the gold standard for confirming or excluding underlying pathology for the perimesencephalic subarachnoid hemorrhage.